Evaluation of Noise Exposure and Hearing Threshold Levels Among Call Centre Operators - Małgorzata PAWLACZYK-ŁUSZCZYŃSKA; Małgorzata ZAMOJSKA-DANISZEWSKA; Kamil ZABOROWSKI; Adam DUDAREWICZ (Archives of Acoustics, 2019)
The aim of this study was to evaluate the hearing status of call centre operators in relation to their noise exposure. Conventional pure-tone audiometry and extended high-frequency audiometry were performed in 49 workers, aged 22–47 years (mean ± SD: 32.0 ± 6.0 years), working in call centre from 1.0 to 16.5 years (mean ± SD: 4.7 ± 2.9 years).